Efficacy and safety of sodium-glucose cotransporter-2 inhibitors for heart failure with mildly reduced or preserved ejection fraction: a systematic review and meta-analysis of randomized controlled trials - Cheema, Huzaifa Ahmad; Shafiee, Arman; Athar, Mohammad Mobin Teymouri; Rafiei, Mohammad Ali; Mehmannavaz, Atefe; Jafarabady, Kyana; Shahid, Abia; Ahmad, Adeel; Ijaz, Sardar Hassan; Dani, Sourbha S.; Minhas, Abdul Mannan Khan; Nashwan, Abdulqadir J.; et al. (Frontiers in Cardiovascular Medicine, 2023)
Aims We sought to conduct a meta-analysis to evaluate the efficacy and safety of sodium-glucose cotransporter-2 inhibitors (SGLT2i) in patients with heart failure (HF) with preserved ejection fraction (HFpEF) and HF with mildly reduced ejection fraction (HFmrEF). Methods We searched the Cochrane Library, MEDLINE (via PubMed), Embase, and ClinicalTrials.gov till March 2023 to retrieve all randomized controlled trials of SGLT2i in patients with HFpEF or HFmrEF. Risk ratios (RRs) and standardized mean differences (SMDs) with their 95% conﬁdence intervals (95% CIs) were pooled using a random-effects model. Results We included data from 14 RCTs. SGLT2i reduced the risk of the primary composite endpoint of first HF hospitalization or cardiovascular death (RR 0.81, 95% CI: 0.76, 0.87; I2 = 0%); these results were consistent across the cohorts of HFmrEF and HFpEF patients. There was no significant decrease in the risk of cardiovascular death (RR 0.96, 95% CI: 0.82, 1.13; I2 = 36%) and all-cause mortality (RR 0.97, 95% CI: 0.89, 1.05; I2 = 0%). There was a significant improvement in the quality of life in the SGLT2i group (SMD 0.13, 95% CI: 0.06, 0.20; I2 = 51%). Conclusion The use of SGLT2i is associated with a lower risk of the primary composite outcome and a higher quality of life among HFpEF/HFmrEF patients. However, further research involving more extended follow-up periods is required to draw a comprehensive conclusion. Systematic Review Registration PROSPERO (CRD42022364223).